2013
DOI: 10.1021/cm303502b
|View full text |Cite
|
Sign up to set email alerts
|

Anatase TiO2 Single Crystals Exposed with High-Reactive {111} Facets Toward Efficient H2 Evolution

Abstract: In this study, for the first time, {111} facet exposed anatase TiO2 single crystals are prepared via both F– and ammonia as the capping reagents. In comparison with the most investigated {001}, {010}, and {101} facets for anatase TiO2, the density functional theory (DFT) calculations predict that {111} facet owns a much higher surface energy of 1.61 J/m2, which is partially attributed to the large percentage of undercoordinated Ti atoms and O atoms existed on the {111} surface. These undercoordinated atoms can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
251
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(268 citation statements)
references
References 55 publications
(85 reference statements)
12
251
1
Order By: Relevance
“…The ESR measurements provided evidence for the presence of Ti 3+ within all the samples, and the magnetic measurements showed that the TB400 sample has a greater saturation n magnetization due to larger amounts of unpaired electrons and hence more Ti 3+ . This correlates well with the dispersive surface energy, where recent reports in the literature have shown that larger surface energy values are due to under-coordinated Ti sites on the surface of the particles (40). The photo-catalysts generate electron hole pairs when excited by UV-Vis radiation, and these eventually form OH or oxygen radicals on the surface of the particles (41).…”
Section: Photocatalytic Activities Of the As-prepared Materials Undersupporting
confidence: 82%
“…The ESR measurements provided evidence for the presence of Ti 3+ within all the samples, and the magnetic measurements showed that the TB400 sample has a greater saturation n magnetization due to larger amounts of unpaired electrons and hence more Ti 3+ . This correlates well with the dispersive surface energy, where recent reports in the literature have shown that larger surface energy values are due to under-coordinated Ti sites on the surface of the particles (40). The photo-catalysts generate electron hole pairs when excited by UV-Vis radiation, and these eventually form OH or oxygen radicals on the surface of the particles (41).…”
Section: Photocatalytic Activities Of the As-prepared Materials Undersupporting
confidence: 82%
“…This shift may be derived from changes of the amounts of functional groups, such as OH group and adsorbed water. 26,27 A similar phenomenon was also observed for NaOH-loaded WO 3 . 20 The absorption of the mixture is sum of the absorption of WO 3 and NaBiO 3 .…”
supporting
confidence: 79%
“…A plane-wave cutoff energy of 300 eV was used in the calculations, which ensured a total-energy convergence of 10 − 4 eV/atom. The surface energy was calculated according to the following equation [30]:…”
Section: Surface Energy Calculationsmentioning
confidence: 99%